Performance, metabolic efficiency and egg quality in Japanese quails fed with acidulated soybean soapstock and lecithin for a prolonged period - BAVARESCO,CAROLINE (2020)
Abstract This study aimed to evaluate the use of acidulated soybean soapstock in association with lecithin on productive performance, metabolic efficiency in the utilization of nutrientes, and the egg quality of Japanese quails. A total of 192 quails were used, distributed randomly in a 2×2×2 factorial scheme that included two types of oils, two levels of supplementation (4% and 8%) and two levels of lecithin (1% or 0%). At the end of the six-month experimental period, some double significant interactions were shown between the level of oil and lecithin for the performance variables (egg weight p=0.04, feed intake p<0.01 and feed conversion rate p=0.04). The feed conversion rate also was influenced by a double significant interaction between the type of oil and the level of oil (p<0.01). The nutrient digestibility showed that different interactions affected the results. The evaluation of egg quality, was verified that the use of acidulated soybean soapstock did not affect most variables of internal quality. The results showed that it is possible to use 8% acidulated soybean soapstock in combination with 1% lecithin in the diets of Japanese quails for a period of up to six months without a reduction in performance.